Juveniles in Criminal Procedure - Lukić, Tatjana; Samardžić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Taking into consideration the importance and role of children in modern society, as well as their position, this article has as its focus juveniles in criminal procedure. The existence of a separate juvenile justice system independent of the criminal law applicable to the adult offenders and general criminal procedure, as well as the periodic changes of the dominant approach in theory and practice reflects the ascendancy of different theoretical perspectives in the juvenile justice. In this paper, the authors scrutinize the models of responding to juvenile crime - justice and welfare model - as two models of the greatest importance in the present reaction of the society to the crimes conducted by the youngest delinquents at the beginning of the new century and millennium. Furthermore, the paper deals with a matter of international legal standards which, to a large extent, give shape to the legal framework for juvenile offenders and provide their rights and position in the criminal procedure. The authors refer to the internationally accepted documents on several levels. From the (almost) universally accepted multilateral conventions on human rights, through the field of recommendations, rules and guidelines which are obeyed and enforced in practice of the juvenile justice although they are of non-binding nature, via the regional European legislative to the national provisions in a particular number of countries. On all the levels mentioned above the rights of the juveniles are regulated having in mind their possible role in the criminal procedure as a perpetrator of a criminal act, as a victim or as a witness. This paper also analyzes the criminal procedure with respect to juvenile perpetrators of the criminal acts in the Republic of Serbia and compliance of the provisions currently in vigor with the international legal standards contained in the international conventions and other internationally accepted and recognized instruments.
Keywords: rights of the child; criminal law; judiciary; legal standards; juveniles